Communication of emotion via drumming: dual-brain imaging with functional near-infrared spectroscopy - Rojiani, Rahil (Soc Cogn Affect Neurosci, 2018)
Nonverbal communication of emotion is essential to human interaction and relevant to many clinical applications, yet it is an understudied topic in social neuroscience. Drumming is an ancient nonverbal communication modality for expression of emotion that has not been previously investigated in this context. We investigate the neural response to live, natural communication of emotion via drumming using a novel dual-brain neuroimaging paradigm. Hemodynamic signals were acquired using whole-head functional near-infrared spectroscopy (fNIRS). Dyads of 36 subjects participated in two conditions, drumming and talking, alternating between ‘sending’ (drumming or talking to partner) and ‘receiving’ (listening to partner) in response to emotionally salient images from the International Affective Picture System. Increased frequency and amplitude of drum strikes was behaviorally correlated with higher arousal and lower valence measures and neurally correlated with temporoparietal junction (TPJ) activation in the listener. Contrast comparisons of drumming greater than talking also revealed neural activity in right TPJ. Together, findings suggest that emotional content communicated by drumming engages right TPJ mechanisms in an emotionally and behaviorally sensitive fashion. Drumming may provide novel, effective clinical approaches for treating social–emotional psychopathology.